The Role of Teaching Quality and its Components on Developing Critical Thinking in Students: Opportunities and Challenges of Curriculum in Higher Education - hamideh pakmehr; hosen jafari sani; mahmood saeedi rezvani; hosen karashki (مطالعات روانشناسی تربیتی, 2012)
Since critical thinking is one of the main goals of university education system and quality is one of the main attributes of educational systems, identifying quality factors effecting critical thinking of students is necessary. So the purpose of present study is to investigate the role of teaching quality and its 4 components-including Lesson plans, teaching performance, teaching and assessing interpersonal relationships- in critical thinking of students. This paper is a correlation survey. Findings showed 1- There is a significant relation between teaching quality and students'' critical thinking (p